2005
DOI: 10.1093/aje/kwi178
|View full text |Cite
|
Sign up to set email alerts
|

Underascertainment of Deaths using Social Security Records: A Recommended Solution to a Little-Known Problem

Abstract: Complete and accurate ascertainment of vital status is of great importance in cohort studies. Recently, during the vital status ascertainment phase of an ongoing occupational mortality study, the authors discovered a potentially serious problem with use of the Pension Benefit Information Company's tracing service or any tracing that relies on records from the Social Security Administration (SSA) Death Master File to identify deaths. Their investigation revealed that a number of US states restrict the informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…Finally, although vital statistics linkages were helpful to identify deceased individuals, access to these resources may be limited by privacy legislation, and the data may not be available in a timely fashion [21]. We found that vital statistics data were incomplete a year after the end of study recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although vital statistics linkages were helpful to identify deceased individuals, access to these resources may be limited by privacy legislation, and the data may not be available in a timely fashion [21]. We found that vital statistics data were incomplete a year after the end of study recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Personal identifier information from the DMDC database was matched to data in the Social Security Administration (SSA) Death Master File (DMF) and SSA Office of Research, Evaluation and Statistics (ORES) Presumed Living Search to determine vital status [16,17]. For those not matched, a commercial tracing service was used to determine vital status.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 Subjects with "unknown" vital status were untraceable mainly due to missing Social Security numbers, a limitation of the original study due mostly to Warners employees hired before the establishment of the SSA. For deaths occurring before 1979 (beginning of NDI), death certificates were obtained from the corresponding state health departments and, to conform with the original study, were coded by a nosologist to underlying cause of death using the 8th revision rules of the International Classification of Diseases (ICD).…”
Section: Cohort Tracingmentioning
confidence: 99%